The Fiduciary Principle as a Pillar of Customer Protection in the Indonesian Banking System - Sartika Fauziah Hafni Harahap (Indonesian Journal of Law and Syariah, 2025)
This study examines the implementation of the fiduciary principle in banking regulations and customer protection mechanisms within Indonesia's banking sector. Employing normative legal research with a statutory and conceptual approach, this study highlights two key findings. First, the fiduciary principle is fundamental to the legal relationship between banks and customers, as stipulated in Article 2 of Law No. 7 of 1992. This principle is reinforced by regulations issued by Bank Indonesia (BI) and the Financial Services Authority (OJK) and is reflected in various aspects of banking operations. These regulations encompass consumer protection, personal data security, financial safeguards, and protection against unfair banking practices. Second, consumer protection mechanisms based on the fiduciary principle are implemented through instruments such as the Deposit Insurance Corporation (LPS), supervision by BI and OJK, and dispute resolution services, including direct complaints to banks, limited facilitation by OJK, and alternative dispute resolution through the Alternative Dispute Resolution Institution (LAPS).This study concludes that the fiduciary principle is crucial for fostering trust, ensuring operational integrity, and promoting stability in the banking sector.